Comparative Evaluation of Implants with Different Surface Treatments Placed in Human Edentulous Mandibles - Muhammad Irfan Khan, Syed Abdul Rauf Shah, Batool Sajjad, Waheed Gul Shaikh, Sameer Quraeshi, Waqar Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Dental implants have reorganized the field of renewing dentistry by providing a greatly successful and authentic surgery option for the patients with missing teeth. Surface characteristics of the implant are very vital for the success of the implant. This greatly affects the osseointegration and long term stability. Study design: It is a prospective study conducted at Lady Reading Hospital, MTI, Peshawar and Altamash Institute of Dental Medicine, Karachi for the duration of one year from December 2021 to November 2022. Material and Methods: The study was done on patients visiting the tertiary care unit for a period of one year. There were 12 male and 13 female patients that participated in the study. The average age of patients was 56 years in case of men and 53 years for women. The data of number of implants was also analyzed and 12 patients went for 2 implants and 13 patients opted for 3 implants. The study was approved by the review and ethical board committee of the hospital. Results: The ISQ score of the patients that had two implants was 68.5±4.3, whereas the patients who went through 3 implants had ISQ score as 72.1±4.5. Those who had molar region implanted had ISQ score 72.1±2.1, while premolar patients had ISQ score as 72.3±3.1. Acid itching group had ISQ score as 68.4±2.4, the LASER group had ISQ score as 73.4±2.4. Conclusion: After the comparison of different implant surfaces used in human edentulous mandibles treatment. It was concluded that the LASER+HA and LASER are the most effective method for implants. These methods accelerates the Osseointegration process. Keywords: Dental implants and edentulous mandibles.